Jurisdiction by Necessity and the Regulation of the Transnational Corporate Actor. Issue 78 (28th February 2014) - Nwapi, Chilenye
This article examines the feasibility of using the jurisdiction by necessity doctrine to promote the accountability of transnational corporations (TNCs) for extraterritorial human and environmental rights abuses committed in developing countries with weak accountability mechanisms. Under the doctrine, a court devoid of jurisdiction may nevertheless hear a dispute where it considers that there is no other court where the dispute may be heard or where the plaintiff may be reasonably expected to bring the action. The article analyzes the inadequacy of existing jurisdictional doctrines in light of the complex web of operations of TNCs, which shields them from the reach of traditional jurisdictional doctrines. After exploring the origin of the jurisdiction by necessity doctrine, the article critically examines the elements of the doctrine to see how they may be applied to the regulation of TNCs. The article argues that the emergence of the jurisdiction by necessity doctrine offers plaintiffs in transnational corporate human rights litigation a new jurisdictional possibility to weigh, as the doctrine has the potential to address some of the jurisdictional difficulties encountered in such litigation.